Experimental metastasis in nude mice of NIH 3T3 cells containing various ras genes. - Bradley, M O (1986)
These studies have compared the ability of NIH 3T3 cells containing different ras oncogenes to form tumor nodules in the lungs of nude mice after tail vein injection. The genes studied include the normal cellular and bladder tumor ras genes, recombinant viral/cellular ras genes, recombinant yeast/mammalian ras genes, and a constructed gene with yeast RAS1 sequences significantly modified by deletions and an oncogenic mutation. The results show that NIH 3T3 cells containing these genes readily form lethal tumor nodules in the lungs of nude mice after tail vein injection. No control NIH 3T3 cells formed lung tumors within 66 days. Although there were some quantitative differences in the potencies of the various lines, the striking conclusion is that NIH 3T3 cells transformed by either normal or activated mammalian ras genes form approximately equal numbers of experimental lung metastases. In addition, cells transformed by a significantly modified yeast RAS1 gene containing a purposefully introduced oncogenic mutation were also equally active in this assay. The amount of p21 (the 21-kDa protein encoded by ras), as measured by immunoprecipitation, was approximately the same in the parent lines before injection as in the tumors recovered after injection. This result indicates that there is no selection for metastatic sublines containing larger quantities of p21. Transfection of EJ bladder tumor ras DNA into NIH 3T3 cells followed by injection 3 days later into the tail veins of nude/beige mice indicated that the EJ ras gene can confer a metastatic phenotype within 3.5 cell generations without selection or clonal growth in vitro. Thus, the biochemical changes initiated after introduction of the c-Ha-ras gene into NIH 3T3 cells result in the almost immediate acquisition of phenotypes necessary for experimental metastasis.